Manajemen Perubahan Kurikulum KTSP 2006 Ke-Kurikulum 2013 Di SMA Negeri 1 Kediri - Bashori (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2016)
This article aims to know (1) the implementation of a change management curriculum KTSP into curriculum 2013; (2) the implication of a change management to learning process; and (3) supports and obstacles factors in the implementation of a change management in SMAN I Kediri. This is a qualitative field research. The subjects are chosen using purposive sampling and snowball sampling. The data are collected by using interview, observation, and documentation. The technique of data analysis uses descriptive qualitative through inductive approach. The findings show that first the implementation management process of curriculum KTSP into curriculum 2013 in SMAN 1 Kediri consists of planning, organizing, actuating and controlling. In practice, the four steps run effectively. However, the controlling process still has not run effectively yet and real in the field. Second, the change management implied on the role of guidance and counseling (BK), the label of department (interest), teacher’s book and student’s book, lesson concept, assessment concept, and scientific approach. Third, the supports factors of the curriculum 2013 implementation in SMAN 1 Kediri are RSBI status, full day school, the students, teachers, and curriculum analysis. The obstacles factors are book procurement, facilities, and financial.